The Influence of Various Corporate Governance Dimensions on Financial Performance Indicators: An Empirical Study of Cement Companies Listed on the Pakistan Stock Exchange - Dr Yousaf Khan,; Muhammad Waseem Arshad,; Junaid ul Hassan,; Sania Batool,; Muhammad Usman, (Dialogue Social Science Review (DSSR), 2024)
This study investigates the influence of corporate governance dimensions on financial performance indicators, specifically Return on Equity (ROE) and Return on Assets (ROA), in cement companies listed on the Pakistan Stock Exchange (PSX). A quantitative approach is employed to analyze 20 active firms using data from PSX, NBP, and other reputable sources from 2011 to 2023. Various statistical models, including Pooled OLS, Random Effects, and Fixed Effects, are evaluated. The Fixed Effects Model is identified as the most robust and reliable for the analysis. Board independence, board activity, CEO duality, managerial ownership, and institutional ownership significantly enhance ROE and ROA. Additionally, board gender diversity, firm size, and firm age positively influence financial performance. Financial leverage exhibits a weakly significant negative impact on performance, while board size does not significantly affect ROE or ROA. The models demonstrate moderate explanatory power (Adjusted R²: 0.352 and 0.330), highlighting the substantial role of corporate governance practices in explaining financial performance variations. The study provides updated empirical evidence specific to Pakistan's cement sector, filling a research gap on the relationship between corporate governance dimension and financial performance indicators in emerging markets. The findings emphasize the importance of adopting structured and inclusive governance practices to optimize financial performance. These insights are crucial for corporate leaders, policymakers, and investors aiming to improve governance standards and competitiveness. Sound governance practices promote sustainable financial performance and ethical business conduct, fostering sector-wide improvements and economic stability. The study focuses solely on the cement sector in Pakistan, which may limit the generalizability of the findings to other industries or regions. Future studies could explore the influence of external factors, such as regulatory frameworks and market dynamics, on the relationship between corporate governance and financial performance. Expanding research to other industries or regions would provide a broader understanding of governance practices in emerging economies.